Peculiarities of Japan’s multinationalism: facts and theories - OZAWA, T. (PSL Quarterly Review, 2014)
A variety of theories have been advanced to explain the present trend of business firms toward multinational operations, first noticed in the United States but now spreading to other industrial countries. The theoretical works thus far have revolved around the behaviour of Western multinationals, with their Japanese counterparts being either treated as a special case or as mere newcomers who will inevitably follow the same path. The differences found in the industrial pattern of Japanese multinationals, however, call for further and more systemic analysis. The present work describes and interprets the uniqueness of Japan’s emerging multinationalism and considers the applicability of existing theories. The author first describes the patterns and competitiveness of Japanese multinationals, before evaluating the relevance of existing Western theories as applied to the Japanese case. JEL: F23